Dietary Patterns in Association With Hypertension: A Community-Based Study in Eastern China - Cuicui Wang; Cuicui Wang; Yanmin Zheng; Ya Zhang; Ya Zhang; Dong Liu; Dong Liu; Li Guo; Bo Wang; Hui Zuo; Hui Zuo (Frontiers in Nutrition, 2022)
ObjectiveThis study aimed to explore the association between dietary patterns and hypertension based on a community–based survey in Suzhou, Eastern China.MethodsThis cross–sectional analysis was undertaken from the subset of the Suzhou Food Consumption and Health State Survey in 2018–2019. Adults aged ≥ 18 years were invited to participate in this survey. Dietary intake was collected by a 24–h dietary recall and a weighing method over three consecutive days (including two weekdays and one weekend day). Dietary patterns were defined using factor analysis. Association between the dietary patterns and hypertension was examined by multivariable logistic regression models with adjustment for covariates. Moreover, sensitivity analysis was used to reinforce our findings.ResultsA total of 2,718 participants were included in the final analysis. Rice-vegetable pattern, fast food pattern, fruit-dairy pattern, and wheat-meat pattern were identified. We observed that the fruit-dairy pattern was inversely associated with hypertension after adjustment for all the covariates (OR = 0.55; 95% CI: 0.40, 0.75; P = 0.002). The association between the wheat-meat pattern and hypertension was attenuated and became statistically nonsignificant in sensitivity analyses. The other two patterns were not significantly associated with hypertension (P > 0.05).ConclusionThe fruit-dairy pattern was inversely associated with the risk of hypertension among Chinese adults. Our findings further emphasize the important role of optimal diet combination in the prevention of hypertension.